Pelatihan Penulisan Laporan PTK pada Guru MIN Se-Kota Palembang (JIP Jurnal Ilmiah PGMI, 2019)
This service aims to provide training and guidance on the writing of CAR reports to MIN teachers in Palembang City and to publish articles on the results of reports and CAR CAR articles throughout Palembang City with seminars on CAR reports. Research methods with PAR (Participatory Action Research). The result of this service is that the training was held twice in two madrasas. Presenters in the training are Fuaddilah Ali Sofyan, M.Pd. Participants who took part in the training were all MIN teachers in the city of Palembang. Teachers are given Modules and examples of CAR reports when training. The training was held for 6 JP and ended with a question and answer session. Researchers were assisted by 2 lecturers of UIN Raden Fatah Palembang. Researchers formed the PTK Whatsapp Group for MIN teachers. The results of the agreement of the teachers from the seminar will be promoted by the number of articles collected, namely 24 articles.